Supramolecular complexes of poly(3‐Hexylthiophene)‐block (and random)‐poly[3‐(2‐(6‐carboxyhexyl)methyl)thiophene] copolymers with perylene bisimide - Shinde, Shekhar (Journal of Polymer Science Part A: Polymer Chemistry, 2018)
Block and random copolymers of poly(3‐hexylthiophene) and poly[3‐(2‐(6‐carboxyhexyl)methyl)thiophene] with side‐chain carboxylic functionality ((P3HT‐b‐P3COOH) and (P3HT‐r‐P3COOH) were developed by Grignard Metathesis (GRIM) polymerization. The carboxylic functionality was introduced in the side chain via the oxazoline route. Both the block and random polythiophene copolymers were complexed with pyridine functionalized perylene bisimide to obtain supramolecular block and random polymer complexes. The complex formation in both systems was confirmed by 1H NMR, WXRD and SAXS studies. An expansion of d spacing upon complex formation was observed in both the block and random copolymer, which could be traced by WXRD. Hole and electron mobilities measured for the supramolecular complexes indicated values which were higher by an order of magnitude for the supramolecular block complex (μh ≈ 2.9 × 10−4 cm2/Vs; μe ≈ 3.1 × 10−6 cm2/Vs) as compared to the random (μh ≈ 1.4 × 10−5 cm2/Vs; μe ≈ 4.7 × 10−7 cm2/Vs) copolymer. These results are indicative of the higher degree of disorder prevailing in the films of random copolymer system compared to the block copolymer.
Keywords: block and random polythiophene; perylene bisi-mide; Self-assembly